The Tsunami and the Chit Fund- Evidence from the Indian Ocean Tsunami Hit on Credit Demand in South India - Kristina Czura; Stefan Klonner (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
We analyze the effects of the 2004 Indian Ocean Tsunami on credit demand in South India. Combining data from a semi-formal financial intermediary with geophysical data on the Tsunami, we estimate the extent to which the price of credit and the structure of credit flows changed in response to this shock. We find a significant increase in the interest rate by 5.3 per cent on average in the affected branches around the Tsunami. Interest rates increased most dramatically in the first three months after the Tsunami hit and decreased subsequently over the year 2005. We conclude that (i) funds provided by Roscas did play a role for coping with this huge negative shock, (ii) repercussions of the Tsunami in the Rosca credit market were limited in terms of the order of magnitude of effects, and (iii) semi-formal credit and official aid are substitutes as disaster coping mechanisms rather than complements.
Keywords: 330; Roscas; Credit and Savings Associations; Rural Finance; Microfinance; Coping Strategies; Natural Disaster; Impact Evaluation